Impact of changing diagnostic criteria on the diagnosis of serrated polyposis syndrome - McWhinney, Connor D.; Lahr, Rachel E.; Lee, Christopher J.; El-Rahyel, Ahmed; Rex, Douglas K. (Endoscopy International Open, 2023)
Background and study aims The World Health Organization criteria for serrated polyposis syndrome (SPS) were established in 2010 and modified in 2019. Neither set of criteria have been validated against genetic markers or proven to be the optimal criteria for defining colorectal cancer risk in patients with serrated colorectal lesions. In this study, we sought to gain insight into how frequently the change in SPS criteria in 2019 impacted the diagnosis of SPS.Patients and methods We reviewed 279 patients with SPS diagnosed between 2010 and 2019 using the 2010 criteria (n = 163) or since 2019 using the 2019 criteria (n = 116). We reviewed whether patients in each group met the diagnosis of SPS by the alternative criteria.Results Of those diagnosed using 2010 criteria, 5.5 % did not meet 2019 criteria. Of those diagnosed by 2019 criteria, 10.3 % did not meet 2010 criteria. Conclusions Most patients with SPS in our database met the diagnosis of SPS by both 2010 and 2019 criteria, with only 5 % to 10 % of patients in each cohort not meeting the alternative diagnostic criteria.